The science of laboratory and project management in regulated bioanalysis. (May 2014) - Unger, Steve; Lloyd, Thomas; Tan, Melvin; Hou, Jingguo; Wells, Edward
Pharmaceutical drug development is a complex and lengthy process, requiring excellent project and laboratory management skills. Bioanalysis anchors drug safety and efficacy with systemic and site of action exposures. Development of scientific talent and a willingness to innovate or adopt new technology is essential. Taking unnecessary risks, however, should be avoided. Scientists must strategically assess all risks and find means to minimize or negate them. Laboratory Managers must keep abreast of ever-changing technology. Investments in instrumentation and laboratory design are critical catalysts to efficiency and safety. Matrix management requires regular communication between Project Managers and Laboratory Managers. When properly executed, it aligns the best resources at the right times for a successful outcome. Attention to detail is a critical aspect that separates excellent laboratories. Each assay is unique and requires attention in its development, validation and execution. Methods, training and facilities are the foundation of a bioanalytical laboratory.